Sintesis dan Karakterisasi Ni/MCM-41 dengan Metode Hidrotermal - Admi; Radiatun Mardiah; Syukri Arief (Departemen Kimia Universitas Andalas, 2022)
Synthesis of mesoporous silica (MCM-41) and mesoporous silica grafted with metal ion Ni(II) to form material (Ni/MCM-41) has been successfully carried out using the hydrothermal method. The results of the MCM-41 X-Ray Diffraction (XRD) characterization show a strong peak at 2q of 1.260 due to the reflection plane (100) and a very weak signal at 2q of 3.0° and 3.3° which corresponds to the reflection plane (110) and (200). The XRD pattern at this small angle indicates that MCM-41 material has been formed. MCM-41 is used as a support for grafting Ni(II) metal ions. After the Ni(II) metal ion was grafted to form Ni/MCM-41 material, the diffraction peak pattern did not change, but only a shift of the diffraction peak to the left (at a smaller angle), namely (100); (110) and (200) of 10°; 2.8°, and 3,0°. This proves the loading of 1% Ni(II) metal ions; 3% and 5% did not change the structure of MCM-41. Based on the FTIR results, the grafting of Ni(II) metal ions has been successful. Evidenced by the decrease in the absorption intensity of surface silanol groups in the range 3700-3200 cm-1 the number has decreased. This result was strengthened by a decrease in the intensity of the siloxane groups (Si-O-Si) in the range of 1250-1000 cm-1. Further evidence is strengthened by the appearance of a new vibrational band below 1000 cm-1 (980-1000 cm-1) which proves the existence of the Si-O-M+ (Si-O-Ni2+) spectrum. The results of this FTIR characterization prove that it has been successful in modifying the surface silanol groups of MCM-41 with metal ion Ni2+ to form Ni/MCM-41.